Preparing special exercises to develop target speed with short distances and some basic skills in junior football players - Zayer, Mohammed Ali Majeed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this study was to prepare special exercises to develop the target speed in short distances and some basic skills for young football players, as well as to determine the effect of these exercises. The researcher used the experimental method by designing two equivalent groups (control and experimental) according to the pre and post-tests. The research community was determined by 200 football players of the Baghdad governorate clubs (9 clubs), the junior category participating in the league for the season 2021/2022. The research sample was chosen deliberately and consisted of 20 junior players of the Al-Naft Sports Club (Peshmerga club hall). They were divided into two groups (control and experimental) in a random way through lottery and each group consisted of 10 players. The search data was processed through the Statistical Package for the Social Sciences (SPSS). The results of our study showed statistically significant differences between the pre-test and the post-test in favor of the post-test (p < 0.05). Also, the experimental group outperformed the control group in the post-test (p < 0.05). In conclusion, the special exercises that were prepared by the researcher showed that they have a great effect on the research variables, and that the experimental group showed a greater development than the control group. The method of repetitive training used in this research contributed positively to the development of speed and skills. It is very important to adopt and benefit from these special exercises designed by the researcher in the development of research variables when training young football players.